Theses on Lenin’s Political Economy after Marx (World Marxist Review, 2025)
Vladimir Lenin is often thought of as a political theorist and politician. His contributions to political economy are often not given the credit as they deserve. His writings on capitalism are exemplars of the class approach to political economy. His work on imperialism innovatively develops some of the themes from Marx’s general law of accumulation in Capital, Vol. 1. Lenin remains wedded to the labour theory of value, theory of surplus value and the doctrine of the proletariat-led class struggle. While an avowed internationalist, he is deeply sensitive to the specificities of the Global South as Marx was. Lenin’s political economy utilizes empirical data which he interprets on the basis of scientific theory with the help of the philosophy materialist dialectics. Lenin also draws political implications of his ideas for the radical transformation of the world. This his political economy offers a unique combination of philosophy, theory, concrete analysis, and guidelines for political practice. The political economy discourse in Lenin’s time and in our time suffers from a series of problems as it offers many revisionist and inaccurate claims. These include denial of, or underemphasis on, numerous facts/processes in capitalist society such as the tendency towards class differentiation; impoverishment of workers; inevitability of periodic crises; importance of value relations; relevance of capitalist imperialism; and so on. The political economy discourse in Lenin’s time and in our time suffers from a series of problems as it offers many revisionist and inaccurate claims. These include denial of, or underemphasis on, numerous facts/processes in capitalist society such as the tendency towards class differentiation; impoverishment of workers; inevitability of periodic crises; importance of value relations; relevance of capitalist imperialism; and so on. Lenin’s political economy responds to these problems and advances a Marxist alternative on many of these themes.